2015
DOI: 10.1177/0963721415605257
|View full text |Cite
|
Sign up to set email alerts
|

Stereotype (In)Accuracy in Perceptions of Groups and Individuals

Abstract: Are stereotypes accurate or inaccurate? We summarize evidence that stereotype accuracy is one of the largest and most replicable findings in social psychology. We address controversies in this literature, including the long-standing and continuing but unjustified emphasis on stereotype inaccuracy, how to define and assess stereotype accuracy, and whether stereotypic (vs. individuating) information can be used rationally in person perception. We conclude with suggestions for building theory and for future direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
119
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(144 citation statements)
references
References 26 publications
18
119
0
5
Order By: Relevance
“…This interpretation is consistent with a recent study by Kirkegaard & Bjerrekaer (2016), who found that Danish people's estimates of welfare use rates for 70 origin country groups correlated at r = .70 [.55, .80] with the actual use rates for those groups. 4 Both of the preceding findings are in line with a larger body of research on stereotype accuracy for demographic groups (Jussim, 2012;Jussim, Crawford, & Rubinstein, 2015; and see Landy, Guay & Marghetis, 2017).…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…This interpretation is consistent with a recent study by Kirkegaard & Bjerrekaer (2016), who found that Danish people's estimates of welfare use rates for 70 origin country groups correlated at r = .70 [.55, .80] with the actual use rates for those groups. 4 Both of the preceding findings are in line with a larger body of research on stereotype accuracy for demographic groups (Jussim, 2012;Jussim, Crawford, & Rubinstein, 2015; and see Landy, Guay & Marghetis, 2017).…”
Section: Introductionsupporting
confidence: 72%
“…Stereotype accuracy is commonly examined at both the individual (personal) level and the aggregate (consensual) level (Jussim et al, 2015). Each of these levels has its own benefits.…”
Section: Aggregate Stereotypesmentioning
confidence: 99%
See 1 more Smart Citation
“…Jussim, Crawford, and Rubinstein (2015) suggest a three-step empirical process when assessing stereotype accuracy, namely (a) assessing people's descriptive beliefs about a group, (b) identifying criteria that establish group characteristics, and (c) comparing beliefs to criteria. In comparing beliefs to criteria, Jussim and colleagues suggest that a discrepancy of more than 20%, or a correlation r < .25, indicates an inaccurate stereotype.…”
Section: Are Gamers Predominantly Male?mentioning
confidence: 99%
“…This is also the approach to stereotypes and stereotyping generally found in entrepreneurship research, where it is mostly used in relation to gender roles (see for example Gupta et al 2009). However, other scholars argue for the opposite, claiming that 'stereotype accuracy is one of the largest and most replicable findings in social psychology' (Jussim et al 2015). Another body of literature revolves around the 'kernel of truth hypothesis' (Prothro and Melikian 1955), which poses that 'stereotypes are based on some empirical reality.…”
Section: Methodsmentioning
confidence: 99%